Complex wound care by a nurse practitioner in primary care: a quality improvement evaluation on healing rates, costs and patient satisfaction. (1st December 2021) - Taidouch, Amal; Crouwers, Marie-José; Spigt, Mark
Abstract : Complex wounds are a major burden for healthcare professionals. Patients with complex wounds are often referred to hospitals or wound expertise centres. Complex wound care could be organised in primary care, but very little published evidence for this is available. In this study, members of a primary healthcare organisation were interviewed to ascertain how the wound care was organised. Patient characteristics and data regarding wound care, healing rates and costs were collected from medical records. Patients filled in a questionnaire concerning accessibility, communication, medical counselling and the overall experience of their treatment. This study followed 25 patients with a total of 42 wounds. Some 82% of the wounds were healed within a mean treatment duration of 9.7 weeks. Mean treatment costs were calculated at €155 (£130) for healed patients. Patients were generally very satisfied with their treatment, illustrated by an overall 8.7 out of 10 scoring on an amended survey based on the Consumer Quality Index. Treating complex wounds in primary care seemed adequate, with high patient satisfaction and tolerable costs.